Field experiment on a scaled prototype of a floating multi-purpose offshore platform: Dynamic response determination with uncertainty quantification. (December 2022) - Ruzzo, Carlo; Malara, Giovanni; Collu, Maurizio; Santoro, Anita; Fiamma, Vincenzo; Scialò, Andrea; Lagasco, Fabrizio; Arena, Felice
Abstract: This paper presents the results of a field experimental campaign on a 1:15 scaled prototype of an innovative floating multi-purpose platform, developed within "The Blue Growth Farm" (BGF) EU H2020 project. The critical technical innovation of the concept is the integration of an industrial aquaculture production system, installed in deep waters, with wind and wave energy harvesting technologies. The article describes the overall structure dynamics based on the analysis of a wide experimental dataset (comprising 5974 records), collected between May and July 2021 at the Natural Ocean Engineering Laboratory (NOEL) of Reggio Calabria (Italy). Specifically, (linearized) response amplitude operators (RAOs) associated with variable environmental conditions are chosen as response indicators, and a comprehensive parametric analysis has been carried out, to assess the optimal criteria for their estimation from the experimental data. The results allowed the identification of the key dynamic properties of the platform concept, including nonlinear effects involved in the overall system dynamics. Furthermore, the novel framework developed here can also be utilized for the analysis and interpretation of other field experimental campaigns on floating offshore structure models.